Application of PRECEDE‐PROCEED model to tackle problems identified with diarrhoea burden among under‐5s in Botswana. (May 2015) - Popoola, Tosin; Mchunu, Gugu
Abstract : Diarrhoea has been identified as the second leading cause of mortality among under‐5s and also claims more life than HIV, measles and malaria combined together in the same category of population. This article is a combination of literature review and personal experience of lessons learnt from past diarrhoea outbreaks in Botswana that caused significant rate of mortality among under‐5s. The paper used literature review to identify contributory factors to diarrhoea burden among under‐5s in Botswana and applied a community health nursing framework (PRECEDE‐PROCEED) to tackle the problems identified. The study revealed that Botswana mothers are lacking in knowledge related to exclusive breastfeeding, prevention and treatment of diarrhoea disease. The paper recommends that health‐care workers in Botswana be sensitized on current diarrhoea management to tailor their health education methods appropriately.